What's economics worth? Valuing policy research - Pardey, Philip G.; Smith, Vincent H. (International Food Policy Research Institute, 2004)
In an era of limited research resources and limitless research needs, demonstrating the worth of any research discipline to policymakers and administrators is a prerequisite for obtaining future funding and making an impact in policy matters. Economists have worked diligently in developing both quantitative and qualitative indicators of the value of science and technology R&D. At the same time, they have paid little or no attention to valuing their own work. In What's Economics Worth? Valuing Policy Research, several expert economists take an important first step towards redressing this imbalance. Anyone who wants to understand what economists do and how to think about valuing their work will find this book intriguing and worthwhile.